Physical, optical and electrical studies on hybrid Ag NPs/NiSi NWs electrode as a DNA template for biosensor - Nazarudin, Nur Fatin Farhanah; Rizan, Nastaran; Periasamy, Vengadesh; Rahman, Saadah Abdul; Goh, Boon Tong (IOP Publishing, 2019)
By means of Chemical Vapor Deposition (CVD), Nickel silicide nanowires (NiSi NWs) were grown on silica substrate followed by a solid-diffusion controlled growth mechanism at different substrate temperatures ranging from 400 to 520 °C. The NWs were then subsequently decorated with Ag nanoparticles (Ag NPs) via a simple thermal evaporation technique. The morphologies of the NiSi NWs and Ag NPs/NiSi NWs showed noticeable dependence on the growth substrate temperatures. NiSi NWs grown at 470 °C exhibited the highest NW density with a uniform decoration of spherical Ag NPs of ∼13.7 ± 1.5 nm of diameter. The Ag NPs/NiSi NWs appeared to exhibit a better crystallinity compared to the as-grown NiSi NWs, which could be attributed to metal induced crystallization. Moreover, the decoration of Ag NPs on NiSi NWs showed a significant enhancement in Raman peak intensities mainly in the Ni2Si, NiSi, and NiSi2 phases. The Ag NPs/NiSi NWs demonstrated a well-defined surface plasmon resonance absorption bands centered at around 420 nm, which elucidate the effectiveness of the decoration of Ag NPs on NiSi NW surfaces with a thin amorphous dielectric barrier layer. Using current-voltage (I-V) measurement, Ag NPs/NiSi NWs and NiSi NWs shown to exhibit a surface type Schottky diode with rectifying behavior. The values of ideality factor for the NiSi NWs and Ag NPs/NiSi NWs Schottky diodes were calculated to be 6.992 and 2.559 respectively. Additionally, the values of series resistances were also calculated , where the series resistance obtained are 91.856 and 38.697 kΩ for NiSi NWs and Ag NPs/NiSi NWs DNA electrodes, respectively. © 2019 IOP Publishing Ltd.